Unidad de formación y desarrollo de negocios portuarios del Magdalena (2018)
The Magdalena River basin is one of the regions with the highest incidence for the country's productivity, this being one of the most important fluvial channels due to the connection between the exterior and the interior of the country. However, the productivity and quality of life of these territories has been declining in recent decades, due to the lack of technology in river ports, pollution in natural resources and the lack of technology and job training, which guarantee the emphasis in territorial vocations, and innovation for the economic boom of the region. Within the mentioned problems, the lack of higher education and labor technification is established as a factor of relevance, since it generates a productive stagnation within the innovation in port processes, as well as limits the supply of jobs for the inhabitants of the region. as a result, the decrease in the quality of life of the inhabitants and the low coverage of unsatisfied basic needs for riparian households. For this reason, a partial plan of development and mitigation, within the educational axis, is proposed for the region of the middle and lower basin of the Magdalena River, specifically within the city of Barranquilla as connection territory and incident infrastructure for the riverine municipalities. and logistics, which provides a series of equipment for the recovery and progress of the area, according to the port infrastructure and environmental resources for economic reactivation through one of the most important fluvial axes at a national level such as the Magdalena River.